Sosialisasi Perkalian dengan Metode Jarimatika pada Siswa SD Buah Hati Padang - Dewi Devita; Deby Erdriani; Laila Marhayati (Pusat Riset dan Inovasi Nasional, 2023)
Community Service (PKM) is a form of the Tridharma of Higher Education. This PKM is proposed to carry out socialization and educational activities. The basic material in learning mathematics at the elementary school level starts with addition, subtraction, to multiplication and division of numbers. But in the multiplication and division material, many students experience difficulties. Actually there are many learning methods that are used to make it easier for students to understand and memorize multiplication. One of them is the jarimatics method. In this method students are not required to memorize but students are taught to be able to understand multiplication by using their limbs, namely their fingers. With jarimatika students will learn multiplication easily and fun. The method used in this PKM is education and hands-on practice of the jarimatics method in multiplication problems. As a result, students become more aware of multiplication and feel happy with the method being taught, because it makes it easier for them to calculate multiplication.